Sewage solutions (advanced version). - Russell, Geoff (Video Education Australasia, 2022)
This program looks at the problem of human sewage waste (both domestic and industrial) and the biological and chemical methods involved in proper treatment. It also examines the costs and benefits of these processes, and the health and safety issues for their operators